Molecular and Immune Characteristics for Lung Adenocarcinoma Patients With ERLIN2 Overexpression - Liu, Yifei; Xie, Pengfei; Jiang, Daishang; Liu, Jian; Zhang, Jianguo; Bian, Tingting; Shi, Jiahai (Frontiers in Immunology, 2020)
Background: Endoplasmic reticulum lipid raft-associated protein 2 (ERLIN2) is protein contained in the membrane of the endoplasmic reticulum. In lung adenocarcinoma (LADC), the molecular function of ERLIN2 and the correlation between ERLIN2 and tumor-infiltrating immune cells has been unclear. The aim of our study was to determine the role of ERLIN2 in LADC development to provide a better understanding of the molecular pathogenesis of this disease and identify new therapeutic targets for its treatment. Methods: Immunohistochemistry, Western blotting, and real-time quantitative polymerase chain reaction were used to detect protein and mRNA levels of ERLIN2 in LADC and adjacent normal tissues. Using the A549 cell line, ERLIN2-short hairpin RNA was applied to silence ERLIN2 to determine its role in LADC cell proliferation and invasion. Based on mRNA expression of ERLIN2 from the Cancer Genome Atlas (TCGA) database, we identified ERLIN2-related protein-coding genes and analyzed the Kyoto Encyclopedia of Genes and Genomes pathway to explore its potential biological functions and determined the correlation between ERLIN2 and tumor-infiltrating immune cells. Results: ERLIN2 was abnormally expressed in a variety of tumor tissues and is highly expressed in LADC. This overexpression was associated with histological grade (P = 0.044), TNM stage (P = 0.01), and lymph node metastasis (P = 0.038). Patient overall survival was poorer with ERLIN2 overexpression. Downregulation of ERLIN2 inhibited LADC cell proliferation and invasion in vitro. Based on mRNA expression of ERLIN2 from the TCGA database, 13 ERLIN2-related genes and 10 pathways were identified and showed a correlation between ERLIN2 and naive B cells and neutrophils. Conclusion: ERLIN2 could serve as a potential diagnostic and prognostic biomarker for LADC and has demonstrated to be correlated with immune infiltrates, which suggests that it may represent a new therapeutic target for LADC.